2021
DOI: 10.21203/rs.3.rs-568177/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hexacyanometallate aqueous flow battery

Abstract: Aqueous redox flow batteries (RFBs) have attracted significant attention as energy storage systems by virtue of their inexpensive nature and long-lasting features. Although all-vanadium RFBs exhibit long lifetimes, the cost of vanadium resources fluctuates considerably, and is generally expensive. Iron–chromium RFBs take advantage of utilizing a low-cost and large abundance of iron and chromite ore; however, the redox chemistry of CrII/III generally involves strong Jahn–Teller effects. Herein, we introduce a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…[ 32 ] The second behavior is that E 1/2 shifts to a higher potential as the scan rate increases, indicating a more dominant shift of E a , which is hindered by Na‐ion desertion ( k l.str ) (e.g., J–T effect). [ 33,34 ] Third, E 1/2 remains unchanged as the scan rate increases, indicating a reversible insertion and desertion of Na ions without any of the aforementioned obstacles. For 1 m SIC, E 1/2 tends to decrease at the reaction of CMn I/II and CMn II/III because Na ions, solvated by a large organic solvent, cause rapid concentration gradient (low k el ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ] The second behavior is that E 1/2 shifts to a higher potential as the scan rate increases, indicating a more dominant shift of E a , which is hindered by Na‐ion desertion ( k l.str ) (e.g., J–T effect). [ 33,34 ] Third, E 1/2 remains unchanged as the scan rate increases, indicating a reversible insertion and desertion of Na ions without any of the aforementioned obstacles. For 1 m SIC, E 1/2 tends to decrease at the reaction of CMn I/II and CMn II/III because Na ions, solvated by a large organic solvent, cause rapid concentration gradient (low k el ).…”
Section: Resultsmentioning
confidence: 99%
“…This greater reversibility of redox kinetics suggests that no significant side reactions take place. 45 More recently, Jang et al 174 reported a novel Fe-Cr RFB framework by employing the strong field cyanide ligand (CN À ) to diminish the impact of Jahn-Teller 175 distortion and enhance the operating voltage with trivial hydrogen evolution. The reported novel electrolyte, K 3 [Cr(CN) 6 ], exhibited a lower redox potential of À1.15 V SHE , retaining the stability against the HER and suppressing cross-over effects owing to the bulk size of [Cr(CN) 6 ] 4À , which coupled with a strong field p-acceptor ligand (CN À ) possesses vacant orbitals that interact with the d orbitals of the metal, leading to the stabilization of t 2g orbitals.…”
Section: Approach Based On Chelating or Strong-field Ligandsmentioning
confidence: 99%